Openness, neuroticism, conscientiousness, and family health and aging concerns interact in the prediction of health-related Internet searches in a representative U.S. sample - Bogg, Tim; Vo, Phuong T. (Frontiers in Psychology, 2014)
Recent estimates suggest 60 % of the U.S. adult population uses the Internet to find health-related information. The goal of the present study was to model health-related Internet searches as a function of an interdependent system of personality adaptation in the context of recent health and aging-related concerns. Assessments of background factors, Big Five personality traits, past-month health and aging-related concerns, and the frequency of past-month health-related Internet searches (via Google, Yahoo, AOL, Bing, or some other search engine) were obtained from a representative U.S. sample (N = 1,015). Controlling for background factors, regression analyses showed more frequent health-related Internet searches were predicted by a drive for exploration and investigation (high openness), as well as alarm sensitivity (high openness and high neuroticism) and an anticipatory inclination (high openness and high conscientiousness) in the context of recent problems with aging parents and recent health concerns for a family member. Consistent with interdependent models of personality adaptation, as well as prior evidence for “surrogate” health-related Internet searches, the results suggest a personality process model of search behavior that is partially dependent upon dispositional levels of exploration, emotional stability, control, and health and aging concerns for family members.